2016
DOI: 10.1186/s40529-016-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, anti-inflammatory, and antidiabetic effects of the aqueous extracts from Glycine species and its bioactive compounds

Abstract: BackgroundThe aim of this study was to examine the possible antioxidant, anti-inflammatory, and antidiabetic effects of the aqueous extracts from three Glycine species. In HPLC analysis, the chromatograms of three Glycine species were established. Flavonoid-related compounds might be important bioactive compounds in Glycine species.ResultsThe results showed that the aqueous extract of Glycine tabacina (AGTa) had the strongest antioxidant activity compared with the other Glycine species extracts. We also found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Flavonoids which are abundant in various medicinal herbs and food sources are well-known for their protective roles in renal disorders such as diabetic nephropathy, glomerulonephritis and kidney insufficiency [49]. High total polyphenols content and total flavonoids content have been reported in aqueous extract of G. tabacina and four common dietary flavonoids (daidzein, genistein, daidzin and genistin) were identified by HPLC analysis [13]. In the present study, we revealed that six flavonoids, i.e.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Flavonoids which are abundant in various medicinal herbs and food sources are well-known for their protective roles in renal disorders such as diabetic nephropathy, glomerulonephritis and kidney insufficiency [49]. High total polyphenols content and total flavonoids content have been reported in aqueous extract of G. tabacina and four common dietary flavonoids (daidzein, genistein, daidzin and genistin) were identified by HPLC analysis [13]. In the present study, we revealed that six flavonoids, i.e.…”
Section: Discussionsupporting
confidence: 50%
“…Benth, a well-known folk medicine and Chinese herbal medicine, is a leguminous plant which is mainly distributed in Australia, the Ryukyu Islands, southern China, and some South Pacific Islands. Its roots have been utilized for the treatment of osteoporosis, nephritis, rheumatism and menopausal syndrome in folk medicine [13,14]. In addition, G. tabacina is also famous as one of the sources of the folk medicine 'I-Tiao-Gung' and serves as a herb tea in Taiwan [13].…”
mentioning
confidence: 99%
See 3 more Smart Citations